Growth and Convergence in WAEMU Countries - Wane, Abdoul (IMF Working Papers; Working Paper ;, 2004)
This paper investigates convergence and dynamic effects of human and physical capital on growth, in WAEMU countries. Using recently developed models for panel data and a growth accounting model, the study finds that growth is largely explained by changes in literacy rates and factor accumulation, but not by growth of total factor productivity (TFP). Nevertheless, the panel estimation identifies aid, government spending, credit to the private sector, and openness as positive determinants of TFP growth, and government deficits as a negative determinant. The study also finds that per capita income in lower-income WAEMU countries converge to per capita income in higher-income ones when economic policies are similar. These results suggest opportunities for policymakers to enhance growth and convergence.